Career Self-Efficacy and Future Career Anxiety on Indonesian Fresh Graduates During Pandemic - Elfina, May Lia; Andriany, Devina (Jurnal Kajian Bimbingan dan Konseling, 2023)
The uncertain job vacancy presents substantial influence on job seekers during the Covid-19 pandemic. The anxiety concerning their future career emerges as a new and deteriorating issue for fresh graduates. On the other hand, self-efficacy serves as a crucial element in facing a shift in the situation. The self-efficacy being adopted in overcoming career anxiety is known as career self-efficacy. Therefore, this study aims to identify the correlation between career self-efficacy and future career anxiety in Indonesian fresh graduate. This study used a quantitative method with a correlational study approach. For the research sample, the final-year students participated in this study and were selected using random sampling. The data were collected through Career Self-Efficacy and Future Career Anxiety instruments and analyzed using data product moment analysis. Our results suggested a negative correlation between career self-efficacy and future career anxiety. Therefore, someone with higher self-efficacy presents a low rate of future career anxiety.